2016
DOI: 10.1139/cjpp-2015-0602
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide down-regulates bleomycin-induced pulmonary fibrosis

Abstract: Keyword:https://mc06.manuscriptcentral.com/cjpp-pubs AbstractWe have found that eIF3a plays an important role in bleomycin-induced pulmonary fibrosis, and up-regulation of eIF3a induced by TGF-β1 is mediated via the ERK1/2 pathway. Whether ERK1/2/ eIF3a signal pathway is involved in CGRP-mediated pathogenesis of bleomycin-induced pulmonary fibrosis remains unknown. Pulmonary fibrosis was induced by intratracheal instillation of bleomycin (5 mg/kg) in rats.Primary pulmonary fibroblasts were cultured to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(16 reference statements)
2
13
1
Order By: Relevance
“…Many studies report that when A549 cells are stimulated with TGF-β, the cells begin to produce mesenchymal cell proteins such as vimentin, desmin, N-cadherin, α-SMA, fibronectin and collagen instead of epithelial cell markers such as Ecadherin, cytokeratin and zonula okludens-1. In other words, they convert their epithelial phenotype into mesenchymal phenotype [25,28,29]. In the present study, GRP did not stimulate the differentiation of A549 cells into myofibroblasts via EMT, whereas it was able to differentiate MRC5 fibroblast into myofibroblasts.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Many studies report that when A549 cells are stimulated with TGF-β, the cells begin to produce mesenchymal cell proteins such as vimentin, desmin, N-cadherin, α-SMA, fibronectin and collagen instead of epithelial cell markers such as Ecadherin, cytokeratin and zonula okludens-1. In other words, they convert their epithelial phenotype into mesenchymal phenotype [25,28,29]. In the present study, GRP did not stimulate the differentiation of A549 cells into myofibroblasts via EMT, whereas it was able to differentiate MRC5 fibroblast into myofibroblasts.…”
Section: Discussioncontrasting
confidence: 62%
“…The most important contribution of TGF-β signalling to the pathogenesis of pulmonary fibrosis is the stimulation of myofibroblast differentiation. The increased TGF-β1 signalling in the lungs enables the differentiation of various cell types, particularly fibroblasts and type 2 pneumocytes, into myofibroblasts [29,35]. Unlike normal lungs, TGF-β1 expression is increased in lung tissue of IPF patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the information about the contribution of α-CGRP on liver fibrosis and cellular senescence during cholestatic liver injury. However, other studies have demonstrated that α-CGRP plays an anti-fibrotic role in pulmonary fibrosis 38 and in liver fibrosis due to hepatitis induced by repeated administration of concanavalin A 39 . This discrepant role of α-CGRP-regulated in fibrosis may be due to mediators of different organs and different animal models of liver injury used.…”
Section: Discussionmentioning
confidence: 95%
“…Pulmonary fibrosis is often complicated by PAH, and it is implicated as a major participant in PAH and is currently being studied as a new therapeutic target [ 51 , 52 ]. The development of MCT-induced pulmonary fibrosis is characterized by an initial inflammatory process with upregulation of pro-fibrotic markers; it increases progressively in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%